Meningkatkan Kemampuan Motorik Kasar Melalui Parenting Senam Masal Ibu dan Anak Pada Anak Usia Dini TK Dharma Wanita Bangsal Kecamatan Pesantren Kota Kediri Tahun Pelajaran 2017/2018 - Subroto, S Edy (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2018)
This research is based on the observation and experience of the researcher, that Based on the observation that happened, the low of abusive motor ability of the child due to not maximally the school implement the learning program involving the component of the student guardian. The problem of this research is whether the parenting program of Gymnastics of Mother and Child can raise gross motor in early child of TK Dharma Wanita Bangsal Kecamatan Pesantren Kota Kediri Lesson Year 2017/2018. Action Research This class also includes descriptive research because it describes how a learning is applied and how the results are to be achieved. Research Action School with the subject of mother and child research in kindergarten Dharma Wanita Bangsal Pesantren Kediri District was conducted in 2 cycles. From the results of the implementation of cycle II which amounted to 85.71% showed the gross motor motor increase early child has reached the completeness that has been determined. Based on the results of school action research conducted at TK Dharma Wanita Bangsal Kecamatan Pesantren Kediri City can be concluded that through parenting activities Gymnastics mothers and children can raise gross motorik early childhood in kindergarten Dharma Wanita Bangsal Kecamatan Pesantren Kota Kediri lesson 2017/2018.